A Social Justice Legitimacy to Protect Coastal Residents - Syaprillah, Aditia; Zein, Yahya Ahmad; H.Malloy, Tove (Journal of Human Rights, Culture and Legal System, 2023)
This research aimed to establish the legitimacy of protecting coastal residents from a social justice perspective. This was normative legal research conducted following cases, statutes, facts, and comparisons. The results of this study show how important it is to prioritize social equity for coastal protection. As natural calamities become more frequent, property protection becomes more difficult. Countries endowed with substantial financial and human resources can effectively tackle the challenges associated with climate change mitigation through the development and establishment of state-of-the-art scientific and technological infrastructure. In multicultural social justice, all individuals are valued. Priorities for environmental and social justice are prevalent in developing nations afflicted by coastal ecological degradation and widening income gaps. Developed nations like Germany have implemented and enforced coastal protection policies to uphold environmental justice principles. Second, the community-led governance initiatives generated genuine participation through mutual aid. Environmental law advances the cause of social justice. Environmental justice, which emphasizes the distribution of resources and the preservation of vulnerable groups, has emerged as the essence of justice in the ecological age.